Microbial Biodiversity of Tang and Pirgal Mud Volcanoes and Evaluation of Bio-Emulsifier and Bio-Demulsifier Activities of Capnophile Bacteria - Parsia, Yasaman; Sorooshian, Shahryar (Elsevier Inc., 2017)
The data presented in this article is related to the Master thesis; entitled “Survey Aerobic Microbial Diversity Mud Volcanoes in Chabahar and Khash Ports in Southern Iran” by the first author of this article, year 2011, Islamic Azad University, Iran (reference number (Parsia, 2011) [1] of this article). This article shows microbial biodiversity and evaluates bio-emulsifier and bio-demulsifier abilities of capnophile isolates, in order to introduce a superior isolate for the Microbial Enhanced Oil Recovery (MEOR) process in the petro chemical industry.